A design of experiment strategy for quality control of specialty coffee drink based on sensory analysis and statistical tools - Licarion Pinto; Hilton Lopes Júnior; Enrique Anastácio Alves; Rodrigo Barros Rocha; Alexsandro Lara Teixeira; Jefferson Santos de Gois (Brazilian Journal of Food Technology)
Abstract Sensory analysis is crucial for assessing food and beverage quality, but discrepancies may arise in some cases and make the quality evaluation imprecise even with statistical analysis. This issue can be mitigated by sensory analysis based on the coffee drink nuanced characteristics. Therefore, in this study, six Q-Graders, following the Specialty Coffee Association of America's sensory analysis method, evaluated various samples and the data was evaluated statistically. The experiment employed a multilevel categorical design, encompassing six evaluator levels, 44 sample levels, and two types of quality assessment. Grades were assigned to the 44 samples using traditional evaluation (no comments) and guided evaluation (prior sample information). It was possible to identify evaluators whose assessments were unbiased across both guided and traditional evaluations. This work introduced a novel strategy to identify biased evaluators, assess the impact of evaluation types, and perform a more accurate assessment of Coffea canephora Pierre ex-Froehner (coffee) quality and assurance assisted with statistical analysis.